Quantum steering on IBM quantum processors - Seifert Lennart Maximilian; Beyer Konstantin; Luoma Kimmo; Strunz Walter T (American Physical Society, 2022)
We use contemporary quantum computers to experimentally investigate quantum steering of an open quantum system by measurements on its environment. On three IBM quantum processors we distinguish a qubit as the open system and perform pairwise interactions with multiple environment ancillas, following a collision model approach. Different measurement strategies on the ancillas lead to different state ensembles of the open system, which are reconstructed by employing state tomography. The amount of steering within the resulting assemblages is quantified with the help of a semidefinite program. We successfully observe the presence of quantum steering in our experimental simulations and can discriminate the different performance qualities and noise levels of the selected quantum devices.